Molecular basis of thrombophilia - Đorđević Valentina (Journal of Medical Biochemistry, 2014)
Thrombophilia is a multifactorial disorder, involving both genetic and acquired risk factors that affect the balance between procoagulant and anticoagulant factors and lead to increased thrombotic tendency. The severe forms of thrombophilia are caused by a deficiency of natural anticoagulants: antithrombin, protein C and protein S. The advances in DNA technology played an important role in the identification of the exact nature of these deficiencies and opened up new possibilities in genetic research and molecular diagnostics of thrombophilia. The major breakthrough came with the discovery of activated protein C resistance and the Factor V Leiden gene mutation. Shortly afterwards, a variant in the 3' untranslated region of the Factor II gene (FII G20210A) associated with an increased concentration of Factor II in plasma was described. These two gene variants represent the most common thrombophilic genetic risk factors. Recently, a novel prothrombin mutation (c.1787G>T) was identified in a Japanese family with juvenile thrombosis. This mutation leads to impaired inhibition of mutant thrombin by antithrombin, proposing a new mechanism of thrombophilia named resistance to antithrombin. In the last decade, several prothrombotic genetic risk factors have been described, including gene variants associated with defects of natural coagulation inhibitors, increased levels of coagulation factors or their impaired inhibition and defects of the fibrinolytic system. However, most of them are not of diagnostic value, due to their minor or unknown impact on the thrombotic risk. Large-scale DNA analysis systems are now becoming available, opening a new era in the genetic studies of the molecular basis of thrombophilia.